PELATIHAN DESAIN AKTIVITAS PEMBELAJARAN MATEMATIKA DIGITAL DENGAN MENGGUNAKAN DESMOS - Yosep Dwi Kristanto (Universitas Negeri Medan, 2021)
Abstract Desmos is a platform or service that offers a variety of math tools, digital math activities, and curricula to facilitate students’ high-level learning in a joyful way through the web or iOS and Android applications. For teachers, Desmos can be employed to improve the quality of mathematics teaching and learning by facilitating students to perform authentic mathematical activities. Therefore, the present community service activity aims to provide professional development programs for teachers to design digital mathematics learning activities using Desmos. The method used in the present community service was online training using Google Classroom and Zoom. The results of this community service activity indicate that the teachers gave a positive assessment of the training implementation, facilitators, and materials. Also, the teachers acknowledged that the training had provided new knowledge on learning media, sparked the desire of teachers to implement Desmos activities in mathematics teaching and learning, and made the teacher give a positive perception to Desmos. As a follow-up to this training, sustainable community service activities are needed so that the teachers can be more optimal in utilizing and integrating technology in mathematics teaching and learning effectively. Keywords: Desmos; Training; Mathematics Teaching and Learning; Professional Development.